(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Objectives: Ayurveda is one of the oldest codified medical knowledge systems with equal emphasis on curative, preventive, and promotive aspects of health. Ayurveda pharmaceutics was developed from the quest to administer plants, animals, or metals and minerals products in a palatable and longer shelf life modification. The study aims to evaluate and characterize the microbial sp. and their biochemical properties in extrapolating its use as a potent probiotic formulation with multifaceted use. Materials and Methods: The microbial diversity of the formulation was evaluated by isolation followed by its microbial characterization using Gram’s staining, biochemical characterization using catalase assay, and molecular characterization by sequencing the internal transcribed spacer (ITS) region. Results: The study revealed that the bacteria isolated in the present study were Gram-positive, rod-shaped organism that exhibited catalase-positive test. Further, molecular characterization studies using the ITS sequence analysis revealed that the isolated organism showed similarity with that of Bacillus species. Conclusion: Therapeutic efficacy of any formulation depends on the process of its preparation, the kind of microflora that is established during aging or fermentation, and the kind of bioactive compounds released during fermentation. The present study identifies the microorganism that plays a pivotal role in this fermentation process and renders therapeutic properties to Dhanyamala formulation. This study can form the basis for further investigations on formulating this as a promising probiotic supplement.